Oedipus and the cabal: conspiracy theories and the decline of symbolic efficiency - Hughes, Brian (Frontiers in Communication, 2024)
Conspiracy theories are a means by which people make sense of vastly complex webs of cause and effect, contingency, and random chance. Impersonal operations of a political economy thus become personified in the figure of sinister puppet masters controlling the world. Overdetermined historical events become narrativized as plots executed with clockwork timing and perfect secrecy. This study proposes a model for the motives and mechanisms by which complex and ambiguous systems are made fodder for paranoid interpretation in the form of a conspiracy theory. By employing an exegetical close-reading methodology and psychoanalytic interpretation, three meta-conspiracies are identified as symptoms of the process described above: antisemitic theories of globalization, the “Deep State” as seen from the political Left, and vulgar UFOlogy. This study will argue that the impenetrable complexity of our globalized, financialized, hypermediated world agitates our experience of the Symbolic order, that is, the realm of language, logic, law, which acts as the scaffolding to the individual’s psychic sense of place in society. Lacan associates entry into the Symbolic order with the reconciliation of the Oedipal conflict and the Symbolic itself with the figure of the Father. However, the complexity and ambiguity of the Symbolic in our contemporary world produce a crisis in this dynamic, which some have described as a “decline in Symbolic efficiency.” This is particularly acute around events, which give rise to conspiracy theories. The will of the Father becomes unknowable, and the order upon which he insists appears dark and chaotic. Conspiracy therefore refers to turning away from this chaotic order and a “dark return” to the pre-symbolic maternal state, via the recession of the Symbolic into the Real, as a chaotic totalized presence (the conspiracy) stretching to occupy every corner of reality.